Implementing card technology in government: different approaches, different outcomes. Issue 1 (27th August 2021) - Palmer, Richard; Gupta, Mahendra; Brandt, James
Abstract : Purpose: The purpose of this paper is to examine plastic and virtual purchasing card use by US Government agencies, with particular focus on how successful implementation might inform governmental entities of potential improvements in the cost, quality and time associated with the digitization of their procure-to-pay processes. Specifically, the paper will: analyze the evolution of card-based payments by US Government agencies, compare the value stream of plastic and virtual cards to governmental entities, analyze the value of card use as a significant and sustainable contributor to greater governmental efficiency and examine the opportunity in the portability of successful card technology implementation strategy. Design/methodology/approach: The authors examined data published by the US federal government relating to agency budgets and commercial card use and combining it with industry performance metrics, projected potential savings and efficiencies for the government and its agencies. Findings: The US Government acknowledges significant administrative cost savings and cash rebates based on its spending on commercial cards. An analysis of US Government spending indicates that changing patterns of card spending are primarily driven by activities of one agency – the Department of Veterans Affairs (VA). Through the incorporation of advances in card technology, escalation of transaction amounts and leveraging card spending data transparency, the VA has continued to increase its use of and benefit from card technology, while other agencies have languished. By replication of VA strategy, the US Government at large has the potential for billions in card-related savings. Research limitations/implications: The study implies that a large swathe of governmental agencies, after having adopted new technology (e.g. purchasing cards), are hesitant to use the new technology, a problem that afflicts most implementation efforts. Countermeasures to offset agency resistance to change should be considered and deployed. Practical implications: Taxpayers demand much of government. The burden of governmental failure to exploit the benefits of innovation (such as card technology) falls on the shoulders of taxpayers. When the government cannot exploit technologies that are commonly used in the private sector, the failure lowers citizen respect for the capability of government employees and the ability of government writ large to solve problems. Social implications: Governmental failure to exploit the benefits of technology dispirits the citizenry, yielding a desire for change that may be disproportionate to the problem at hand. Originality/value: The study combines General Services Administration, US Treasury and market data points to make a unique assessment of the benefits derived through 20 years of governmental commercial card use.